Hormonal contraception in women with endometriosis: a systematic review. (2nd January 2019) - Grandi, Giovanni; Barra, Fabio; Ferrero, Simone; Sileo, Filomena Giulia; Bertucci, Emma; Napolitano, Antonella; Facchinetti, Fabio
Abstract: Objective: A systematic review was carried out of studies of women with endometriosis, to examine the evidence for efficacy of the use of hormonal contraception to improve disease-related pain and decrease postoperative risk of disease recurrence. Methods: A search of the Medline/PubMed and Embase databases was performed to identify all published English language studies on hormonal contraceptive therapies (combined hormonal contraceptives [CHCs], combined oral contraceptives [COCs], progestin-only pills [POPs] and progestin-only contraceptives [POCs]) in women with a validated endometriosis diagnosis, in comparison with placebo, comparator therapies or other hormonal therapies. Main outcome measures were endometriosis-related pain (dysmenorrhoea, pelvic pain and dyspareunia), quality of life (QoL) and postoperative rate of disease recurrence during treatment. Results: CHC and POC treatments were associated with clinically significant reductions in dysmenorrhoea, often accompanied by reductions in non-cyclical pelvic pain and dyspareunia and an improvement in QoL. Only two COC preparations (ethinylestradiol [EE]/norethisterone acetate [NETA] and a flexible EE/drospirenone regimen) demonstrated significantly increased efficacy compared with placebo. Only three studies found that the postoperative use of COCs (EE/NETA, EE/desogestrel and EE/gestodene) reduced the risk of disease recurrence. There was no evidence that POCs reduced the risk of disease recurrence. Conclusions: CHCs and POCs are effective for the relief of endometriosis-related dysmenorrhoea, pelvic pain and dyspareunia, and improve QoL. Some COCs decreased the risk of disease recurrence after conservative surgery, but POCs did not. There is insufficient evidence, however, to reach definitive conclusions about the overall superiority of any particular hormonal contraceptive.